A Multiple Emergency Ventilator as backup solution for disaster situations: prototype development and functional assessment - Aldo J. Suria; Luca G. Paroni; Silvano Seva; Roberto Viganò; Francesco Casella; Alberto Zanella; Giuseppe Baselli; Gianfranco B. Fiore (Medical & Biological Engineering & Computing, 2025)
Shared ventilation is an interesting topic amongst researchers due to the possibility of healthcare saturation under disaster conditions provoked by viruses, war environments, diffusive respiratory system diseases, etc. However, general outcomes from this practice have shown several risks. The Multiple Emergency Ventilator overcomes these hazards by providing a temporary, pressure-controlled ventilatory support for up to ten patients simultaneously, whilst allowing for a modular and fast assembly during emergencies. This article presents the construction and the assessment of the prototype using patient simulators with different types of bio-mechanical characteristic configurations at ten hospitalization stations. Ventilation parameters at the most distal-to-source station were recorded. Under normal operation, a minute ventilation of 9.6 breaths × L × min −1 was obtained. Critical operation during different types of localized sudden pneumatic disconnections was also investigated. Amongst these, only the event of a disconnection of any simulator at its pneumatic connection to the main distribution pipeline highlighted a poor minute ventilation of 4 breaths × L × min −1 . Yet, the probability of such an event is minimal due to the use of safe mechanical constraints at the relevant pneumatic connections. In this first prototype assessment, the device has shown its capabilities to ventilate multiple patients with consistent pressure behaviours even whilst adverse conditions are imposed. Graphical Abstract

Mapping temporo-parietal and temporo-occipital cortico-cortical connections of the human middle longitudinal fascicle in subject-specific, probabilistic, and stereotaxic Talairach spaces - Nikos Makris; A. Zhu; G. M. Papadimitriou; P. Mouradian; I. Ng; E. Scaccianoce; G. Baselli; F. Baglio; M. E. Shenton; Y. Rathi; B. Dickerson; E. Yeterian; et al. (Brain Imaging and Behavior, 2017)

Human middle longitudinal fascicle: variations in patterns of anatomical connections - N. Makris; M. G. Preti; T. Asami; P. Pelavin; B. Campbell; G. M. Papadimitriou; J. Kaiser; G. Baselli; C. F. Westin; M. E. Shenton; M. Kubicki (Brain Structure and Function, 2013)

An adaptive neuro-fuzzy method (ANFIS) for estimating single-trial movement-related potentials - D. D. Ben Dayan Rubin; G. Baselli; G. F. Inbar; S. Cerutti (Biological Cybernetics, 2004)

Non-invasive model-based estimation of the sinus node dynamic properties from spontaneous cardiovascular variability series - A. Porta; N. Montano; M. Pagani; A. Malliani; G. Baselli; V. K. Somers; P. van de Borne (Medical & Biological Engineering & Computing, 2003)

Analysis of cardiac left-ventricular volume based on time warping averaging - E. G. Caiani; A. Porta; G. Baselli; M. Turiel; S. Muzzupappa; M. Pagani; A. Malliani; S. Cerutti (Medical & Biological Engineering & Computing, 2002)

Information domain analysis of cardiovascular variability signals: Evaluation of regularity, synchronisation and co-ordination - A. Porta; S. Guzzetti; N. Montano; M. Pagani; V. Somers; A. Malliani; G. Baselli; S. Cerutti (Medical & Biological Engineering & Computing, 2000)

Conditional entropy approach for the evaluation of the coupling strength - A. Porta; G. Baselli; F. Lombardi; N. Montano; A. Malliani; S. Cerutti (Biological Cybernetics, 1999)

Performance assessment of standard algorithms for dynamic R-T interval measurement: comparison between R-Tapex and R-Tend approach - A. Porta; G. Baselli; F. Lambardi; S. Cerutti; R. Antolini; M. Del Greco; F. Ravelli; G. Nollo (Medical & Biological Engineering & Computing, 1998)

Quantifying electrocardiogram RT-RR variability interactions - A. Porta; G. Baselli; E. Caiani; A. Malliani; F. Lombardi; S. Cerutti (Medical & Biological Engineering & Computing, 1998)

Measuring regularity by means of a corrected conditional entropy in sympathetic outflow - A. Porta; G. Baselli; D. Liberati; N. Montano; C. Cogliati; T. Gnecchi-Ruscone; A. Malliani; S. Cerutti (Biological Cybernetics, 1998)

Classification of coupling patterns among spontaneous rhythms and ventilation in the sympathetic discharge of decerebrate cats - A. Porta; G. Baselli; N. Montano; T. Gnecchi-Ruscone; F. Lombardi; A. Malliani; S. Cerutti (Biological Cybernetics, 1996)

Single sweep analysis of visual evoked potentials through a model of parametric identification - S. Cerutti; G. Baselli; D. Liberati; G. Pavesi (Biological Cybernetics, 1987)